The Response of Cladoceran Communities to the Climatic Changes of the Late Holocene Southwestern Québec - Cooper, Emily (Université d'Ottawa / University of Ottawa, 2015)
This thesis focuses on a chronological analysis of the cladoceran communities from a sediment core of a small oligotrophic lake in southwestern Québec, Canada over the past 1250 years. The sediments of the lake were varved, which allowed for accurate dating. A previously published pollen study of the lake provided a record of the paleoclimatic and landscape changes in the region. The core was then used to infer how changes in temperature and landscape changes impacted the taxonomic composition of the cladoceran community through time. Cladoceran diversity was high throughout most of the Medieval Warm Period and into the Little Ice Age and decreased during the modern period in response to increased temperatures and anthropogenic impacts. Daphnia and plant-associated species greatly decreased in the past 100 years. This shift, combined with increased temperatures and changes in the landscape opened up a niche for the colonization by the smaller Bosmina longirostris. The modern communities are unlike most of what was observed throughout the past millennium.
Keywords: Paleolimnology; Cladocera; Climate change; ecology